Breeding performance of the Blue Tit Parus caeruleus in a patchy Mediterranean landscape - Catalan, R M; Haeger, J F (REVUE D ECOLOGIE-LA TERRE ET LA VIE, 1999)
This study compares reproductive strategy and breeding success of Parus caeruleus in a helm-oak (Quercus rotundifolia) forest and a pine plantation (Pinus pinea and P. pinaster) in the southern Iberian Peninsula. During the breeding period, an asymmetric flow of individuals takes place from the helm-oak forest to the pine plantation. This flow is favoured by nestboxes where Blue tits can lay their eggs. During the winter, a large part of the population moves back from the pine plantation to the helm-oak forest. Breeding pair density was much higher in the helm-oak forest than in the pine plantation. This may bt accounted for by the poorer quality of the resources available in the pine plantation which birds try to compensate for with larger breeding territories. Breeding density and most life-history traits examined (timing of breeding, clutch site, egg size, number of fledglings and fledgling weight) were similar in both habitats, as a result of the phenotypic plasticity of this species. Although breeding success was similar in both habitats, recruitment of new individuals per unit area was higher in the helm-oak forest. The consequences of pine plantations, as a form of forestry management, on species conservation is discussed.
APS
Keywords: breeding success; Holm oak; iberian peninsula; Parus caeruleus; Pinus pinaster; Pinus pinea; Quercus ilex; reproductive strategies

NO EFFECTS OF A FOREST SPRAYING OF MALATHION ON BREEDING BLUE TIPS (PARUS-CAEREULEUS) - Pascual, J A (ENVIRONMENTAL TOXICOLOGY AND CHEMISTRY, 1994)
Ultra low volume (ULV) aerial spraying of the organophosphorus insecticide malathion is widely used in Spain to control Tortrix viridana, the most important lepidopteran pest of Spanish holm oak forests (Quercus ilex). A field study was carried out in spring 1988 to analyze the short-term effects of a standard application rate of malathion (1, 160 g a.i./ha) on the breeding success of the blue tit (Parus caeruleus). Several blue tit reproductive parameters and seasonal variation of arthropod densities in canopy trees (focusing on caterpillars, the main food resource for breeding blue tits) were compared between a malathion-treated plot and a control plot. None of the breeding parameters (nest abandonment, nest success, hatching success, nestling mortality, daily survival rate, and nestling weight) showed differences between the treated and the control plots. Malathion spraying caused nearly a 100% mortality of the target pest Tortrix viridana, but it did not reduce availability of another Tortricidae (Archips xylosteana), with the result that food supply was similar or higher in the treated plot than in the control plot. The main conclusion of this study is that a forest standard application of malathion did not cause adverse short-term effects on breeding blue tits. Moreover, this work focused on the indirect effects of insecticides via food depletion; its results suggest that in these kinds of studies it is more important to assess the abundance of arthropods remaining alive after treatment than the degree of arthropod mortality caused by the insecticide.
Keywords: BLUE TIT (PARUS-CAERULEUS); breeding success; FOREST SPRAYING; Indirect effects; MALATHION